2021
DOI: 10.1089/heq.2020.0062
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Disparities Among the Black Population and Their Influence on the Equitable Management of Chronic Pain

Abstract: Introduction: Growing evidence suggests disparities in the prevalence, management, progression, and outcomes of chronic, nonmalignant pain-related conditions, especially for African American patients. Objective: The purpose of this review is to explore studied causative factors that influence the management of chronic pain among African Americans, including factors that result in disparate care that may contribute to unfavorable outcomes. Methods: This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…It is important to note that because our examination of race and gender in the effects of pain on drinking was exploratory, with observed power values below recommended levels (e.g., 0.8; Serdar et al, 2021), these findings warrant replication and should be interpreted with caution. Nonetheless, given evidence of racial bias in pain assessment and treatment, and known disparities regarding the management of chronic pain among Black/African American populations (Hoffman et al, 2016; Knoebel et al, 2021), additional investigation into the role of pain in patterns and trajectories of alcohol consumption among Black drinkers is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that because our examination of race and gender in the effects of pain on drinking was exploratory, with observed power values below recommended levels (e.g., 0.8; Serdar et al, 2021), these findings warrant replication and should be interpreted with caution. Nonetheless, given evidence of racial bias in pain assessment and treatment, and known disparities regarding the management of chronic pain among Black/African American populations (Hoffman et al, 2016; Knoebel et al, 2021), additional investigation into the role of pain in patterns and trajectories of alcohol consumption among Black drinkers is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the pain of Black Americans is often underdiagnosed and undertreated in the US, compared to that of their White counterparts. 37,38 The racial disparities may, in part, result from clinician factors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the pain of Black Americans is often underdiagnosed and undertreated in the US, compared to that of their White counterparts. 37 , 38 The racial disparities may, in part, result from clinician factors. In experimental studies, participants showed more stringent thresholds for perceiving pain on Black faces, compared to White faces.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent large national case–control study, African‐American/Black individuals were significantly less likely to receive outpatient rehabilitation than their white counterparts (odds ratio = 0.89) 88 . Specific to pain management, African‐American persons continue to experience disparities in the prevalence, management, progression, and outcomes of chronic, nonmalignant pain‐related conditions 89 …”
Section: Common Neurologic Sequelae and How To Best Guide Carementioning
confidence: 99%
“…88 Specific to pain management, African-American persons continue to experience disparities in the prevalence, management, progression, and outcomes of chronic, nonmalignant pain-related conditions. 89…”
Section: Initial Treatment Approachmentioning
confidence: 99%